Hearing loss in adult women with Turner's syndrome and other congenital hypogonadisms. (February 2014) - Ros, Cristina; Tercero, Anna; Alobid, Isam; Balasch, Juan; Santamaria, Joan; Mullol, Joaquim; Castelo-Branco, Camil
Abstract Objectives: To define the patterns and causes of hearing decline associated to Turner's syndrome (TS). Methods: An observational study with three cohorts was designed: 31 TS patients, 15 women with other congenital hypogonadims (OCH) and 41 healthy age-matched women taking contraception. Microotoscopy, standard pure-tone audiometry brain auditory evoked potentials (BAEP) were performed to study hearing function. Results: Up to 87% of TS subjects suffered from some degree of hearing loss (HL) in the audiograms, compared with 20% OCH and 27% controls. Sensorineural hearing loss (SNHL) was the most frequent type of hypoacusia found in TS group. BAEP study demonstrated that 61% of TS women showed HL compared to 20% in OCH patients. No significant differences in latencies, amplitudes, and interpeaks of waves I, III and V were found between TS and OCH, nor when compared to reference population. Worse results were observed among the oldest TS patients, those with pure monosomy or isochromosome, and those with a history of recurrent otitis. Conclusions: More than a half of TS females presented HL. SNHL is the most frequent pattern among middle-aged women with TS. Old age, karyotype and recurrent otitis are predisposition factors to produce HL, while oestrogens play a minor role.